Assignment of the human gene for the low density lipoprotein receptor to chromosome 19: synteny of a receptor, a ligand, and a genetic disease. - Francke, U (1984)
The availability of a species-specific monoclonal antibody that recognizes the low density lipoprotein (LDL) receptor of human but not hamster origin permitted assignment of the structural gene for the human receptor to chromosome 19. The antibody was used to detect the human LDL receptor in a series of hamster-human somatic cell hybrids by two assays: (i) a structural assay that measured cellular incorporation of [35S]methionine into immunoprecipitable receptor and (ii) a functional assay that measured the rate of receptor-dependent uptake and degradation of the 125I-labeled anti-receptor monoclonal antibody. Both assays showed that the human LDL receptor was expressed in 15 out of 20 hybrid cell lines. Expression of the human LDL receptor was 100% concordant with the presence of human chromosome 19; all other human chromosomes showed at least 25% discordance. As expected, the gene for the LDL receptor (LDLR) is located on the same chromosome as the gene for the disease familial hypercholesterolemia, which has been previously mapped to chromosome 19 by pedigree studies and is caused by allelic mutations at the LDL receptor locus. The gene for apolipoprotein E, a ligand for the LDL receptor, is also known to be located on chromosome 19, raising the possibility of an evolutionary link between a protein ligand and its receptor.